2010
DOI: 10.4067/s0301-732x2010000200006
|View full text |Cite
|
Sign up to set email alerts
|

Recording of bioelectrical activity changes in sheep cerebral cortex

Abstract: RESUMENEl objetivo de este estudio es presentar el uso práctico de la electroencefalografía (EEG), demostrando el aspecto básico de EEG en ovejas, así como su utilidad en el análisis de las alteraciones provenientes del sistema nervioso central. Se examinaron 10 hembras híbridas de Oveja Merino Polaca, seleccionadas especialmente con fines experimentales. Debido a la falta de una fórmula unificada en el método de EEG en animales, se realizó un registro de potenciales provenientes de algunos puntos escogidos tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 58 publications
1
4
0
Order By: Relevance
“…Therefore, the presented results of our experiments were based on the same practice. It was found that there are both beta waves, confirmed earlier by Cwynar and Zawadzki (2010), and also intermittent theta and delta rhythms. Pellegrino and Sica (2004) believe that dogs under sedation, without access to visual stimuli, may be characterised by the appearance of alpha waves, thus having lower values of neural voltage potentials, as well as lower frequencies.…”
Section: Eeg Interpretationsupporting
confidence: 54%
See 1 more Smart Citation
“…Therefore, the presented results of our experiments were based on the same practice. It was found that there are both beta waves, confirmed earlier by Cwynar and Zawadzki (2010), and also intermittent theta and delta rhythms. Pellegrino and Sica (2004) believe that dogs under sedation, without access to visual stimuli, may be characterised by the appearance of alpha waves, thus having lower values of neural voltage potentials, as well as lower frequencies.…”
Section: Eeg Interpretationsupporting
confidence: 54%
“…Yoshida et al (2004) discussed these kinds of inventions and recommended that great attention should be paid towards the interpretation of animal experimental methods. Even so, most authors try to maintain the current convention in wave classification in frequency bands regardless of the EEG wave recording methods (Cwynar and Zawadzki 2010). It was also noted that during the EEG recording in dogs the interpretation and classification of rhythms were made according to the criteria of human medicine, as in the study by Pellegrino and Sica (2004) and Brauer et al (2011).…”
Section: Eeg Interpretationmentioning
confidence: 99%
“…However, in case 1, the voltage was significantly higher (median: 45 µV) than in cases 2 and 4. Also in literature, two studies reported lower voltage values in healthy sheep (Cwynar and Zawadzki 2010;Cwynar et al 2014). Moreover, as reported by Cwynar et al (2014), in case 2, the EEG activity varied depending on the area of the skull in which it was recorded: the beta rhythm had a greater expression in the posterior area while the delta rhythm had a greater expression in the most cranial zones.…”
Section: Discussionmentioning
confidence: 60%
“…Channels located near the temporal line also detected delta wave activity and the activity recorded near the occipital lobes was characterised by a beta rhythm (Cwynar et al 2014). In Polish Merino sheep aged 3-4 years, the EEG were characterised by a beta rhythm with a mean voltage value of 26.5 µV (Cwynar and Zawadzki 2010). There are two mechanisms producing EEG abnormalities in the hydrocephalus: the https://doi.org/10.17221/8/2021-VETMED increased intracranial pressure that induces disturbances in the blood supply -either generally or focally -and cerebral oedema, and degenerative brain lesions secondary to the chronic increase of the intracranial pressure (Klemm and Hall 1971;Redding and Knecht 1984;Armasu et al 2014).…”
Section: Discussionmentioning
confidence: 97%
“…In general, sedation may be used alone or in combination with a general anesthetic and as a premedication in anesthesia induction [7] [8]. Electroencephalogram record electrical activity from the scalp surface using conduction media of metal electrode [9]. EEG waves are distinguished by frequency, amplitude and morphology [3].…”
Section: Resultsmentioning
confidence: 99%